PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA CANCHA SINTÉTICA DE FÚTBOL EN LA PARROQUIA EL CISNE, CANTÓN LOJA - CARRIÓN TENE, JOSÉ LUIS (2019)
THE “PROJECT DE FEASIBILITY FOR THE IMPLEMENTATION DE A SYNTHETIC PLAYING FIELD DE SOCCER IN THE PARISH CHURCH THE SWAN, CANTON LOJA” has like main objective To Accomplish a feasibility study that it enables determining the possibility of implementing a synthetic playing field in the parish church The Swan and that way strengthening the culture pertaining to sports and healthy of the inhabitants of the parish, with the aim of improving his quality of life. In the development of investigation a market research was done for which 122 opinion polls in the parish church applied over themselves The Swan, the same ones that served to obtain information, with the purpose of later on standing trial and obtaining the potential, real and efficacious request. The offer obtained it himself by means of the calculation of the real request, where 240 people practice soccer, but he has in account that not everybody would go to the synthetic playing field, which is why stole half as much people, giving an offer of the 50 %. With it the unfulfilled request was determined. A plan of commercialization comes true, in which provides evidence of his identity the marketing variables, as the Service, the canal of commercialization, the promotion and the price, for which determined strategies in every one of the variables themselves. The technical study allowed location, the installed capacity of 5,460 to determining the size, the location, the microcomputer hour service, the distribution of the plant and the productive process of the service. In the administrative study came true the description of business, the entrepreneurial philosophy, also what concerns the legal company statute, leaving in note the legal steps, for the company constitution as the Unipersonal Company of Responsabilidad Limited, structures 5 it organizational, the structural functional organizational chart and the manual of functions of the performance of every person in the synthetic playing field. And, finally, it finds the cost-reducing study – financier, where it was determined that it takes an amount of $103.182,49 dollars for the total investment, two types of financings, the first one analyze the funds obtained between the three associates in equal shares with a 61 % themselves, second with a financing of the 39 intervening % credit in the BAN- ECUADOR. Also it was determined by means of the indicators of the Financial Evaluation the VAN of $79.544,15, 85.71 %'s, Relación Beneficio Costo's Internal pullback rate of $1,20 dollars, Recuperación's Period of capital of 2 years, 1 month and 3 days, as to the results obtained of the project, it is determined that the project has financial feasibility and can get in operation, the positive values as much in the THEY GO like the TIR, they make The Swan be a feasible investment for the Creation of the synthetic playing field of soccer set inside the parish church.